Analisis Perilaku Generasi Z dalam Mengadopsi Bank Digital : Pendekatan TAM dan S-O-R - Ilham, Teuku Muhammad Rizki; Sihotang, Ellen Theresia (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: The purpose of this study is to determine the factors that influence the adoption of digital banks based on the concept of the Technology Acceptance Model (TAM) in gen-Z. Methods: The data analysis technique uses Structural Equation Modeling (SEM) inferential analysis with WarpPLS 8.0. Research Finding: The results of this study revealed that perceived ease of use (PEOU) and perceived usefulness (PU) have a positive and significant on attitudes (ATT). PEOU indirectly has a positive and significant on PU. PU has a positive and significant effect on behavioral intention (BI). ATT directly has a positive and significant on BI in digital bank adoption. Theoretical contribution: TAM can be applied to measure gen-Z behavior in digital bank adoptions. Practitioner/Policy implication: Digital bank management should consider usability and user-friendliness factors as stimuli for attitudes that generate behavioral intentions towards digital bank adoption, specifically among Gen-Z. This generation serves as a potential target market for digital banking services marketing. The results of this study can drive innovation in digital banking products and services, enhancing operational efficiency for banks. Research limitation: The results of this study are only specific to gen-Z and cannot be generalized